DIFFICULTY FACTORS IN IMPLEMENTING ONLINE TEACHING SKILLS PRACTICE STUDENTS OF BUILDING ENGINEERING EDUCATION STUDY PROGRAM JAKARTA STATE UNIVERSITY - Sinta Dwi Cahyanti; Daryati Daryati; Rosmawita Saleh (LPPM Universitas Negeri Jakarta, 2022)
The research is to know the difficulty factors implementation teaching practice (PKM) online students Building Engineering Education Study Program State University of Jakarta. The research use quantitative descriptive method. The sample is 54 PKM students and 32 tutor teachers SMK field of Building Engineering expertise in Jakarta. The sample are collected using questionnaire and documentation. The result show that difficulty factors implementation PKM online include: conculting with tutor teachers in the preparation RPP, accessing Video Conference, implementing online learning according to the set time, ensuring students are ready for online learning, activate the camera while using Video Conference, explaining learning material, and provide attitudes and skill assessment.